Loudness Perceptions Influence Feelings of Interpersonal Closeness and Protect Against Detrimental Psychological Effects of Social Exclusion. (April 2022) - Wang, Deming; Ziano, Ignazio; Hagger, Martin S.; Chatzisarantis, Nikos L. D.
We propose that perceptions of auditory loudness and interpersonal closeness are bidirectionally related. Across 12 experiments (total N = 2, 219; 10 preregistered; with Singaporean, British, U.S. American, and Australian participants), we demonstrated that louder audio made people feel physically (Study 1a) and socially (Study 1b) closer to others, presumably because loudness activates interpersonal closeness-related concepts implicitly (Studies 1c and 1d). This loudness–interpersonal closeness effect was observed across diverse samples (Studies 2a, 3a, and S1), for longer listening intervals (Study 2b), and in natural settings (Studies 3a and 3b). Conversely, individuals made to feel socially excluded rated their surroundings as quieter (Study 4). Furthermore, following social exclusion, individuals showed a preference for louder volume (Study 5). Finally, exposure to loud stimuli mitigated detrimental psychological effects of social exclusion (Study 6). Theoretical implications for the social cognition of loudness, social exclusion and compensatory strategies, and practical implications for ameliorating loneliness are discussed.